Myths, muses and mortals: the way of life in ancient Greece - Furley, William D. (Reaktion Books, 2024)
"Myths, Muses and Mortals gives new insight into a multitude of life experiences in ancient Greece. The book introduces the lives of the ancient Greeks through extracts taken from a range of sources, including poems, plays, novels, histories, lawsuits, inscriptions, and private note tablets. The voices speak for themselves in fresh translation, but in addition, William Furley gives the narratives historical context and illuminates the literary genre in which they appear. The texts are grouped around important areas of life--love relations, travel and trade, social status, divine signs, daily events, warfare, philosophies, dress code, and private and public celebration--giving voice to the variety of lives experienced by the citizens of ancient Greece and an insight into the Greek mind."
Keywords: Quelle; Sozialgeschichte; Griechenland